KEPUTUSAN LAJNAH TARJIH MUHAMMADIYAH DAN LAJNAH BAHSUL MASAâIL NAHDLATUL ULAMA SEBAGAI KEPUTUSAN IJTIHAD JAMAâI INDONESIA - Sirajuddin, Azmi (ISTINBATH JURNAL HUKUM, 2004)
Ijtihad (Independent Judgment in Legal Questions) is a source of the Islamic law. In the past, the ijtihad was made individually, but in modern time it is probably conducted collectively (Jamaâi). The Muhammadiyahâs Committee of the Tarjih (taking a preponderant legal opinion) and the NUâs Committee of the Bahth al-Masaâil (Research on the Religious Questions) are actually two institutions of the Ijtihad jamaâi (Collective independent Judgment in Legal Questions) in Indonesia. Â Â Â Â Â Â Â Â Â Â Â  Each institution representing opinion of Muhammadiyah and NU organizations has in principle the same concept of Islamic law, but they have differences in the methodology of formulating the law. Keyword : Decisions, Ijtihad Jamaâi